2022
DOI: 10.3390/su14063563
|View full text |Cite
|
Sign up to set email alerts
|

Towards the 2030 Agenda: Measuring the Progress of the European Union Countries through the SDGs Achievement Index

Abstract: The 2030 Agenda and Sustainable Development Goals were adopted by the United Nations in 2015 as a universal call to action to end poverty, protect the planet, and ensure that by 2030 all people enjoy peace and prosperity. The success or failure in their implementation largely depends on the national implementation effort, measured within wide and compound indicator frameworks. Due to such complexity, providing a simple but comprehensive view on the progress to achieve the SDGs is a priority. Moreover, the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The starting point in our research was the Sustainable Development Report 2022, from the analysis of which we observed a series of paradoxes both between the results of the SDG Index and between the results presented in this report and those presented by other researchers (i.e., Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Taajamaa et al, 2022).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The starting point in our research was the Sustainable Development Report 2022, from the analysis of which we observed a series of paradoxes both between the results of the SDG Index and between the results presented in this report and those presented by other researchers (i.e., Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Taajamaa et al, 2022).…”
Section: Introductionmentioning
confidence: 77%
“…Our methodology consists of a critical analysis of literature starting from the Sustainable Development Report 2022, the 2030 Agenda for Sustainable Development, and the representative work of relevant scholars (i.e., Hwang and Yoon, 1981;Bravo, 2014;Costanza et al, 2016;Dhaoui, 2018;Ding et al, 2018;Burlea-Schiopoiu, 2019;Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Sachs et al, 2022;Taajamaa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Sweden's attainments outlined in Agenda 2030 were always between average and the best, placing Sweden as the country that made the most significant progress towards SDGs during the period of 2015-2018. Rocchi et al (2022) presented the evolution of an existing sustainability index in order to measure the progress of EU countries towards the achievement of the objectives of Agenda 2030. They proposed the Sustainable Development Goals Achievement Index (SDG-AI), which represents all the sustainability-related information.…”
Section: Literature Reviewmentioning
confidence: 99%